Análisis cinemático de los saltadores de alto de Antioquia (2007)
ABSTRACT: The purpose of this paper was to analyze biomechanical factors of the high jumpers who integrate the Athletic Antioquia Team and to correlate these factors with the height of the jump. The design of this research was descriptive and correlative. The population and sample were four athletes (3 men, 1 woman) of the Antioquia Team who participate in the Athletic National Championship 2006. The next variables were studied: length and speed of the next to last and last step; thigh angle in the take off; body angle in the take off; height center gravity in the take off and maximal height over the lath; center gravity velocity in the take off; angle and angular velocity of the ankle and knee in the take off; vertical velocity of the wrist and free knee. Silicon Coach and Kinematrix programs were used. SPSS v15 was used in order to calculate statistical parameters. The results show the following positive correlations with the height of the jump: body angle in the last step: (r=-0,62; a=0,031); body angle in the take off (r=-0,88; a=<0,001); thigh angle in the take off (r=-0,59; a=<0,044); vertical velocity of the gravity center in the take off (r=-0,871; a=<0,001); center gravity angle in the take off (r=-0,771; a=<0,003); maximal height of the gravity center elevation (H2) (r=-0,857; a=<0,001)